Repetitive mild traumatic brain injury induces persistent alterations in spontaneous synaptic activity of hippocampal CA1 pyramidal neurons - Ludovic D. Langlois; Prabhuanand Selvaraj; Sarah C. Simmons; Shawn Gouty; Yumin Zhang; Fereshteh S. Nugent (IBRO Neuroscience Reports, 2022)
Mild traumatic brain injury (mTBI) or concussion is the most common form of TBI which frequently results in persistent cognitive impairments and memory deficits in affected individuals [1]. Although most studies have investigated the role of hippocampal synaptic dysfunction in earlier time points following a single injury, the long-lasting effects of mTBI on hippocampal synaptic transmission following multiple brain concussions have not been well-elucidated. Using a repetitive closed head injury (3XCHI) mouse model of mTBI, we examined the alteration of spontaneous synaptic transmission onto hippocampal CA1 pyramidal neurons by recording spontaneous excitatory AMPA receptor (AMPAR)- and inhibitory GABAAR-mediated postsynaptic currents (sEPSCs and sIPSCs, respectively) in adult male mice 2-weeks following the injury. We found that mTBI potentiated postsynaptic excitatory AMPAR synaptic function while depressed postsynaptic inhibitory GABAAR synaptic function in CA1 pyramidal neurons. Additionally, mTBI slowed the decay time of AMPAR currents while shortened the decay time of GABAAR currents suggesting changes in AMPAR and GABAAR subunit composition by mTBI. On the other hand, mTBI reduced the frequency of sEPSCs while enhanced the frequency of sIPSCs resulting in a lower ratio of sEPSC/sIPSC frequency in CA1 pyramidal neurons of mTBI animals compared to sham animals. Altogether, our results suggest that mTBI induces persistent postsynaptic modifications in AMPAR and GABAAR function and their synaptic composition in CA1 neurons while triggering a compensatory shift in excitation/inhibition (E/I) balance of presynaptic drives towards more inhibitory synaptic drive to hippocampal CA1 cells. The persistent mTBI-induced CA1 synaptic dysfunction and E/I imbalance could contribute to deficits in hippocampal plasticity that underlies long-term hippocampal-dependent learning and memory deficits in mTBI patients long after the initial injury.